The Legal Force of Consensual Justice in Economic and Customs-Related Crimes in Jordanian Legislation as Compared to Egyptian Legislation - Al-Drobi, Taha Kaseb; Darawsheh, Alaa Yousef (Dirasat: Shari'a and Law Sciences, 2025)
Objectives: This study aims to demonstrate the legal force of consensual justice in economic and customs-related crimes as a concept, since it is the common denominator between rigorousness in protecting public funds, the initiative to refund such assets, and the repercussions of tampering with them, in light of provisions regulating criminal reconciliation in Jordanian and Egyptian legislation. Methods: The study relies on the comparative approach to compare relevant legislation, while the descriptive and analytical approaches are adopted for legal issues that call for either of these two methods. Results: The paper concludes that Jordanian and Egyptian legislators are rigorous in protecting public funds, while leaving the door open for perpetrators of related crimes to apply criminal conciliation and benefit from ensuing implications, the most importance of which is the termination of the criminal case and the reduction of fines and compensation. Conclusions: This research paper recommends that Jordanian legislators amend the Economic Crimes Law so that the legal provisions of the criminal settlement contract are exhaustive. It further suggests that the current Customs Law be amended so that the reconciliation procedure be restricted to the stage prior to the issuance of the First Instance Court’s ruling, and finally, it recommends that the Egyptian legislator amend the Customs Law so that reconciliation is no longer an option once the criminal ruling becomes final, in order to safeguard the principle of the binding nature of criminal rulings.